Risk Factors of an Influenza A(H1N1)pdm09 Outbreak in a Nursing Institute, Noagaon, Bangladesh, 2015 - Khan, Samsad Rabbani; Billah, Mallick Masum; Monalisa; Billah, Syed Muhammad Baqui; Shirin, Tahmina; Rahman, Mahmudur (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2021)
An H1N1 outbreak in the Noagaon Nursing Institute in Bangladesh allowed examination of risk factors for influenza transmission and a return-to-work policy. We conducted a retrospective cohort study of 119 nursing students residing in the nursing institute’s dormitory. The attack rate of influenza was 51% (61/119) and 28% (5/18) of suspected influenza cases tested positive for influenza A(H1N1)pdm09. Eighty percent of the students returned to their training in the hospital and the classroom three days after the first onset of symptoms. Living in overcrowded dormitories (risk ratios (RR) 1.7, 95% confidence interval (CI) 1.2-2.4), contacting with students with influenza-like illness (RR 2.7, 95% CI 1.6-4.6) placed students at greater risk for receiving and for transmitting influenza. To prevent transmission, we recommended isolating students with influenza during the viral shedding period and annual influenza vaccination.